Use magnified images to help define the boundaries of melanonychia in surgery - He, Simin; Xue, Siliang (The Journal of dermatological treatment, 2025)
The diagnoses of longitudinal melanonychia (LM) may be nail matrix nevus, etc. During excision, factors like small/pale lesions make it hard to define the boundary. Head - mounted magnifiers have limited magnification and intraoperative dermatoscopes are often unavailable. We used a DSLR camera to take and magnify pictures. First estimate the incision, then adjust. This method is recommended for doctors without intraoperative dermatoscopes.